Investigating The Relationship Of Leader Personality And Leader Member Exchange Quality In Malaysian Petrochemical Organizations - Jahangiri, Pouyan (2011)
Leader member exchange theory is the only theory which is systematically concentrated on vertical dyad linkage between leader and follower and it is explored in the early 1970s and many researches examines its effect on different aspects of organizations as outcomes, however, until today there are few researchers focusing on its antecedents for predicting a model for LMX.